2012
DOI: 10.14746/ssllt.2012.2.3.7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pronunciation learning strategies on mastering English vowels

Abstract: The present paper focuses on the role of strategies in learning the pronunciation of the target language. First, an outline of various general classifications of language learning strategies is provided. Next, pronunciation learning strategies are defined and their various taxonomies are presented. This is followed by the description of the study which investigated the influence of pronunciation learning strategies on the perception and production of English pure vowels and diphthongs by first-year students of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…In addition, according to the two main categories, the results which were congruent to the study's result of Rokoszewska (2012) reveal that the indirect strategies were mostly utilized among both groups (69.34% and 68.86%). That is, in the category of direct strategies, cognitive strategies showed the highest frequency use (72.56% and 70.84%); in other words, the use of affective strategies was the highest in the category of indirect strategies (73.76% and 71.08%).…”
Section: Pronunciation Language Learning Strategiessupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, according to the two main categories, the results which were congruent to the study's result of Rokoszewska (2012) reveal that the indirect strategies were mostly utilized among both groups (69.34% and 68.86%). That is, in the category of direct strategies, cognitive strategies showed the highest frequency use (72.56% and 70.84%); in other words, the use of affective strategies was the highest in the category of indirect strategies (73.76% and 71.08%).…”
Section: Pronunciation Language Learning Strategiessupporting
confidence: 75%
“…In addition, experience from out-of-class experiences plays more significant role in L2 pronunciation than in-class experience. Unlike Szyszka (2015) who focused on pronunciation learning strategies from advanced learners, Rokoszewska (2012) was interested in pronunciation from low proficiency learners. He found that students preferred indirect strategies to direct strategies on their perception and production of English monophthongs (pure vowels) and diphthongs.…”
Section: Pronunciation Learning Strategiesmentioning
confidence: 99%
“…Also worth mentioning in this section are the research projects conducted by Hişmanoğlu (2012), Rokoszewska (2012) and, yet again, Pawlak (2018). In a study involving 38 English majors, Hişmanoğlu (2012) set out to compare the use of PLS of successful and unsuccessful students.…”
Section: The Link Between Pls Use Achievement and Id Factorsmentioning
confidence: 98%
“…The moderate level pronouncers least frequently employed the third strategy of using phonetic symbols or self-devised codes to remember how to pronounce words. Rokoszewska (2012) has investigated the interplay between PLS and perception, as well as production, of English vowels. The participants were 63 first-year English as a foreign language learners, who responded to a 5-point Liket scale questionnaire eliciting data on the frequency of PLS use.…”
Section: Variables Associated With Good L2 Pronunciation Learnersmentioning
confidence: 99%
“…Cognitive internal variables, according to Wrembel (2008), encompass, among others, language aptitude and learning strategies subsuming PLS, which are still underresearched (Berkil, 2009;Eckstein, 2007;Rokoszewska, 2012). The former is defined as "a variety of human traits that are involved in thinking, reasoning, processing information, and acquiring a new knowledge" (Dörnyei, 2005, p. 32).…”
Section: Introductionmentioning
confidence: 99%